(untitled) (Comprehensive Journal of Science, 2025)
The optimal allocation and sizing of capacitors in a Medium Voltage (MV) distribution grid utilizing Particle Swarm Optimization (PSO) for selecting the optimum size and placement of capacitors units can significantly affect the distribution grid. Capacitor installation serves as a standard approach for reactive power compensation. This study focuses on optimizing capacitor allocation and sizing to enhance voltage profiles and minimize power losses. The PSO algorithm, in conjunction with OpenDSS, is used to analyze the power flow outcomes from the IEEE 14 Bus system. To achieve this, the PSO and OpenDSS tools were employed in the research to process the power flow data from the standard IEEE 14 Bus system. The performance of the PSO model was evaluated by presenting the outcomes, demonstrating that the PSO algorithm successfully determines the optimal size and location of capacitors.